Patient aggression experienced by professional nurses in acute psychiatric ward: South Africa - Tshinanne G. Thandavhathu; Mary Maluleke; Ndidzulafhi S. Raliphaswa; Mphedziseni E. Rangwaneni; Thingahangwi C. Masutha; Ndivhaleni R. Lavhelani; Duppy Manyuma; Langanani C. Makhado; Takalani E. Thabathe; Lufuno M. Kharivhe; Vusiwana P. Letlalo; Mulatedzi P. Mulaudzi (AOSIS, 2024)
Background: Aggression of patients in hospital wards has become an endemic problem and professional nurses are particularly at high risk. Aim: This article presents the types of patient aggression experienced by professional nurses working in an acute psychiatric ward in Vhembe District, South Africa. Setting: Vhembe District, South Africa. Methods: A qualitative approach using exploratory, descriptive and contextual research design was used. Four hospitals were purposively selected and 10 professional nurses were conveniently sampled to participate in the study. Individual interviews were used to collect data, which were then analysed through Tesch Open Coding Method. Measures to ensure trustworthiness and ethical considerations were adhered to throughout the study. Results: This study shed some light on the professional nurses' lived experiences regarding the types of aggression from patients in an acute psychiatric ward in Vhembe District. The types of aggression are physical aggression, destructive behaviour and verbal aggression. Conclusion: The findings show that the types of aggression to which professional nurses are exposed are overwhelming and the consequences are shocking. As a result, the health of professional nurses is compromised. Therefore, this study recommends further studies to determine the kind of support needed by professional nurses working in an acute psychiatric ward and to investigate the impact of aggression from patients in acute psychiatric ward with regard to the quality of care. Contribution: This article contributes to the body of knowledge regarding patients' aggression in acute wards in Vhembe District, South Africa.